Cell Adhesion on UV‐Crosslinked Polyurethane Gels with Adjustable Mechanical Strength and Thermoresponsiveness. Issue 24 (21st October 2021) - Breul, Katharina; Stengelin, Elena; Urschbach, Moritz; Mondeshki, Mihail; Wüst, Laura; Sirleaf, Jason; Seitel, Sebastian; Emt, Theresa; Pschierer, Sarah; Besenius, Pol; Seiffert, Sebastian
Abstract: Temperature‐responsive polyurethane (PU) hydrogels represent a versatile material platform for modern tissue engineering and biomedical applications. However, besides intrinsic advantages such as high mechanical strength and a hydrolysable backbone composition, plain PU materials are generally lacking bio‐adhesive properties. To overcome this shortcoming, the authors focus on the synthesis of thermoresponsive PU hydrogels with variable mechanical and cell adhesive properties obtained from linear precursor PUs based on poly(ethylene glycol)s (pEG) with different molar masses, isophorone diisocyanate, and a dimerizable dimethylmaleimide (DMMI)‐diol. The cloud point temperatures of the dilute, aqueous PU solutions depend linearly on the amphiphilic balance. Rheological gelation experiments under UV‐irradiation reveal the dependence of the gelation time on photosensitizer concentration and light intensity, while the finally obtained gel strength is determined by the polymer concentration and spacing of the crosslinks. The swelling ratios of these soft hydrogels show significant changes between 5 and 40 °C whereby the extent of this switch increases with the hydrophobicity of the precursor. Moreover, it is shown that the incorporation of a low amount of catechol groups into the networks through the DMMI dimerization reaction leads to strongly improved cell adhesive properties without significantly weakening the gels. Abstract : Poly(ethylene glycol)‐based polyurethanes with variable cloud point temperatures are UV‐crosslinked to produce soft hydrogels for potential tissue engineering applications. The strength of these hydrogels can be adjusted by precursor concentration and crosslinking density, while the thermal adaptivity is determined by the amphiphilic balance. The modular design approach further allows the incorporation of catechol groups which significantly improves the cell‐adhesive properties.